Effect of Fermentation of Acacia Leaves (Acacia Mangium) Using Aspergillus Niger on Nutrient Content - Sri Sukaryani; Engkus Ainul Yakin; Diyah Kartika Wulan (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2021)
Acacia (Acacia mangium) is a multipurpose plant, useful for fuel, hedge plants, and available throughout the year. Fermentation on acacia leaves needs to be done to reduce crude fiber and increase the dissolved protein content of the feed ingredients. This study aims to determine the effect of the nutritional content of acacia leaves (Acacia magium) fermented using Aspergillus niger as much as 0-2%. The method used in this research is the experimental method of fermenting acacia leaves (Acacia magium). The experimental design used was a completely randomized design (CRD) consisting of three treatments and three repetitions. The treatments were as follows: P0= Fermentation with Aspergillus niger as much as 0% of 300 grams of acacia leaves, P1= Fermentation with Aspergillus niger as much as 1% of 300 grams of acacia leaves, P2= Fermentation with Aspergillus niger as much as 2% of 300 grams of acacia leaves for 7 days . Parameters observed were soluble protein, soluble fat, crude fiber. The average value of crude fat P0: 7.18%, P1: 8.33%, P2:15,47%. The average value of dissolved protein content P0: 2.89%, P1: 2.93%, P2: 3 ,51%. The average value of crude fiber P0: 68.23%, P1: 68.40%, P2: 68.90%. From the results of this study, it can be concluded that Acacia leaves (Acacia Mangium) fermented using Aspergillus niger had a significant effect on crude fat content, but did not significantly affect soluble protein content and crude fiber content of acacia (Acacia Mangium) leaves.